2000
DOI: 10.1002/1097-0207(20000910/20)49:1/2<109::aid-nme925>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Local optimization-based simplicial mesh untangling and improvement

Abstract: We present an optimization‐based approach for mesh untangling that maximizes the minimum area or volume of simplicial elements in a local submesh. These functions are linear with respect to the free vertex position; thus the problem can be formulated as a linear program that is solved by using the computationally inexpensive simplex method. We prove that the function level sets are convex regardless of the position of the free vertex, and hence the local subproblem is guaranteed to converge. Maximizing the min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(69 citation statements)
references
References 11 publications
1
68
0
Order By: Relevance
“…Excellent references on the surprisingly large array of quality metrics employed in practice include [12] and [24]. Some of the worst-element improvement techniques most relevant to the work presented in this paper include [7] which was one of the first to use numerical optimization techniques. While gradient-based optimization methods are often preferred in general practice due to superior convergence rates, the mesh optimization problem is often non-smooth, implying that the gradients are not immediately available.…”
Section: Previous Workmentioning
confidence: 99%
“…Excellent references on the surprisingly large array of quality metrics employed in practice include [12] and [24]. Some of the worst-element improvement techniques most relevant to the work presented in this paper include [7] which was one of the first to use numerical optimization techniques. While gradient-based optimization methods are often preferred in general practice due to superior convergence rates, the mesh optimization problem is often non-smooth, implying that the gradients are not immediately available.…”
Section: Previous Workmentioning
confidence: 99%
“…(5) Take their intersection R by plane sweep (typically in 0(n log n) time). (6) Otherwise, go back to step (4). Fig.…”
Section: Heuristic Algorithmmentioning
confidence: 99%
“…Mesh generation/improvement [5,6,10,12,13] is an important process for many purposes including Finite Element Method. In a simple setting, a given simple polygon is partitioned into many small triangles after inserting an appropriate number of points in its interior as vertices of triangular meshes.…”
Section: Introductionmentioning
confidence: 99%
“…At each position, the quality of surrounding elements is updated and this process is iterated until the optimum is found. It has been demonstrated that the quality function has only one maximum inside the valid domain of the neighbour elements, so the algorithm is guaranteed to converge to the optimal solution [11].…”
Section: Tetrahedral Mesh Generationmentioning
confidence: 99%